Attention Deficits and Thyroid Function - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The relation between attention and thyroid function was examined in 85, 7-year-old, children with congenital hypothyroidism (CH) at the Hospital for Sick Children, Toronto, Canada.